Pembiasaan Nilai-Nilai Islami pada Anak Usia Dini - Febrian, Nanda; Mutmainnah, Mutmainnah; Wulandari, Atika; Ependi, Zulham (Prodi PIAUD STAI Sumatera Medan, 2025)
This study aims to describe the implementation process, supporting and inhibiting factors, and the impact of habituating Islamic values on the religious behavior of early childhood students at RA Yayasan Pendidikan Agama Islam. Using a qualitative method with a case study approach, data were collected through observation, interviews, and documentation involving the head of the RA, teachers, and parents. The findings reveal that the habituation of Islamic values is carried out through daily routines, teacher role modeling, and a religious school environment. The main supporting factors include institutional commitment, teacher involvement, and parental participation, while the obstacles arise from children’s diverse characteristics, inconsistent reinforcement at home, and limited facilities. The habituation of Islamic values has a positive impact on shaping children’s religious behavior, reflected in their growing spiritual awareness, moral discipline, social empathy, and Islamic identity. This study emphasizes that the success of value habituation depends on strong collaboration between schools and families in creating a sustainable ecosystem for Islamic character education.